CAVERNOUS MEDULLARY HEMANGIOMA OF THE DISTAL LEFT FEMUR: A CASE REPORT - Shevchenko, Igor; Hubskyi, Stanislav; Danyshchuk, Zinayda; Zlatnik, Ruslan; Ivanova, Nataliya; Maltseva, Valentyna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Bone hemangiomas occur in only one percent of primary bone neoplasms, and their diagnosis is difficult. The location of these benign neoplasms in long bones is even more rare. Objective. To describe the features of the diagnosis and surgical treatment of a woman with cavernous medullary hemangioma of the distal femur. Methods. The main diagnostic methods were computed tomography, radiography, and histopathological examination of the surgical specimens. Treatment was surgical removal of the neoplasm followed by rehabilitation with dosed loading of the limb. Results. A 45-year-old woman presented to the clinic with persistent aching pain in the left knee joint that did not stop after taking analgesics. Radiologically and using magnetic resonance imaging, an area of destruction and a neoplasm of irregular shape with clear uneven contours were found in the distal epimetaphysis of the left femur. Over 2 years of observation, the volumetric neoplasm did not increase on the radiographs, but the pain syndrome did not disappear and intensified during physical exertion. The results of the trephine biopsy did not allow to determine the exact diagnosis. Surgical treatment was carried outby means of parietal resection of the pathological focus of the distal part of the left femur and combined replacement of the defect with bone allograft with cement and fixation with a plate and screws. Morphological changes detected in the surgical specimens during histopathological examination corresponded to the diagnosis of cavernous hemangioma of the bone. At six months postoperatively, the patient demonstrated nearcomplete painless weight-bearing on the operated limb with minimal use of a cane, and the knee joint’s range of motion was fully restored. Conclusions. Cavernous hemangioma of the femur is difficult to diagnose using trephine biopsy alone; accurate diagnosis is typically possible only through analysis of the surgical specimen. Surgical treatment enabled painless weight-bearing on the left limb by the sixth month of follow-up.